Current Studies of Mitochondrial Quality Control in the Preeclampsia - Peng, Xiaoqing; Hou, Ruirui; Yang, Yuanyuan; Luo, Zhigang; Cao, Yunxia (Frontiers in Cardiovascular Medicine, 2022)
Mitochondria are cellular energy powerhouses that play important roles in regulating cellular processes. Mitochondrial quality control (mQC), including mitochondrial biogenesis, mitophagy, mitochondrial fusion and fission, maintains physiological demand and adapts to changed conditions. mQC has been widely investigated in neurodegeneration, cardiovascular disease, and cancer because of the high demand for ATP in these diseases. Although placental implantation and fetal growth similarly require a large amount of energy, the investigation of mQC in placental-originated preeclampsia (PE) is limited. We elucidate mitochondrial morphology and function in different pregnancy stages, outline the role of mQC in cellular homeostasis and PE and summarise the current findings of mQC-related PE studies. This review provides suggestions on the future investigation of mQC in PE, which will lead to the development of new prevention and therapy strategies for PE.